2018
DOI: 10.1001/jama.2018.2757
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Inhaled Corticosteroids and Long-Acting Muscarinic Antagonists With Asthma Control in Patients With Uncontrolled, Persistent Asthma

Abstract: In this systematic review and meta-analysis, the use of LAMA compared with placebo as add-on therapy to inhaled corticosteroids was associated with a lower risk of asthma exacerbations; however, the association of LAMA with benefit may not be greater than that with LABA. Triple therapy was not associated with a lower risk of exacerbations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 33 publications
3
73
1
Order By: Relevance
“…The triple beclomethasone/formoterol/glycopyrronium 100:6:12.5 combination reduced by '0.5-1 logarithm the concentrations of monocomponents required to produce the same bronchorelaxant effect induced by the dual beclomethasone/formoterol 100:6 combination in human isolated airways, as previously reported (Calzetta, Matera, Facciolo, et al, 2018). Indeed, this finding further supports the superiority of triple therapy compared to single and dual therapy to improve pulmonary function of patients affected by asthma and stable COPD, as recently demonstrated by high-quality meta-analyses (Calzetta et al, 2019;Cazzola et al, 2018;Sobieraj et al, 2018;Zheng et al, 2018). However, further pharmacological investigations are needed to adequately quantify the possible synergistic effect of adding a LAMA to an ICS/LABA combination, but this was outside the scope of this study.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The triple beclomethasone/formoterol/glycopyrronium 100:6:12.5 combination reduced by '0.5-1 logarithm the concentrations of monocomponents required to produce the same bronchorelaxant effect induced by the dual beclomethasone/formoterol 100:6 combination in human isolated airways, as previously reported (Calzetta, Matera, Facciolo, et al, 2018). Indeed, this finding further supports the superiority of triple therapy compared to single and dual therapy to improve pulmonary function of patients affected by asthma and stable COPD, as recently demonstrated by high-quality meta-analyses (Calzetta et al, 2019;Cazzola et al, 2018;Sobieraj et al, 2018;Zheng et al, 2018). However, further pharmacological investigations are needed to adequately quantify the possible synergistic effect of adding a LAMA to an ICS/LABA combination, but this was outside the scope of this study.…”
Section: Discussionsupporting
confidence: 80%
“…The last Global Initiative for Asthma report (GINA, ) and Global Initiative for Chronic Obstructive Lung Disease (GOLD 2019) recommend to combine an ICS with a LABA and a LAMA to treat severe forms of asthma and chronic obstructive pulmonary disease (COPD). The recent quantitative syntheses of data extracted from pivotal clinical trials carried out in asthmatic and COPD patients suggest that administering ICS/LABA/LAMA as fixed‐dose combinations may lead to clinical benefits when compared with single and dual combination therapy, namely, LAMA administered as monocomponent and ICS/LABA or LABA/LAMA combinations (Calzetta, Cazzola, Matera, & Rogliani, ; Cazzola, Rogliani, Calzetta, & Matera, ; Sobieraj et al, ; Zheng et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Potential publication bias was evaluated by funnel plots when 10 or more trials were pooled. 18 All statistical analyses were two sided, and a P value of less than 0.05 was regarded as statistically significant. We also used the GRADE approach (grading of recommendations assessment, development, and evaluation) to rate the quality of evidence and generate absolute estimates of effect for the outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…Tiotropium Respimat® has been shown to be an efficacious and well-tolerated add-on treatment to inhaled corticosteroid (ICS) therapy with or without additional controllers, with comparable safety and efficacy to long-acting β 2 -agonists (LABAs) [14][15][16][17][18][19][20][21][22] . A systematic review and meta-analysis comparing the efficacy and safety of tiotropium with that of LABAs as add-on to ICS in patients with uncontrolled persistent asthma aged 12 years and older reported comparable improvements in clinical outcomes 22 . Similarly, in paediatric patients aged 4-17 years with asthma, a recent literature review of LABAs, leukotriene receptor antagonists (LTRAs) and tiotropium reported that tiotropium and LABAs have similar efficacy and provide greater improvements in lung function than LTRAs as add-on to ICS.…”
Section: Defining Asthma Exacerbations and Worseningsmentioning
confidence: 99%